Experience Value: Customer Perspective of Theater Institutions - Wioletta KRAWIEC (Communications of International Proceedings, 2023)
This article explores customer preferences for theater institutions regarding the experience value offered to them. Particular attention was paid to the marketing activities of theaters, which, in addition to traditional offerings, further enhanced visitors' experiences. The survey was conducted on a sample of 798 theatergoers located in 10 major Polish cities. The research showed the strongest statistical significance for theaters' items, such as theater workshops, educational classes, regular repertoire, and artistic performances. This is dictated by the desire to escape from everyday life (as per Pine and Gilmore, 1999). Research showed no relationship between experiences in the entertainment and education groups. Gender, age, education and residence variables were not found to be significant in the decision to choose the type of experience. The behavioral module was the most frequently perceived activity of theaters from the area of strategic experience modules, according to Schmitt (1999). Combining this with the frequency of theater visits, the highest significance of the sensory module emerged. Modular classification-based activities will make sense when customers come to theater institutions at least once a month or more often. People who visit the theater once every few years do not have the opportunity to deepen their experience or experience something special. The research contributes theoretically and practically to discussing consumer experience dimensions, experience planning, and customer experience management in theatre institutions.
Keywords: experience value; types of experience; strategic experience modules; theaters